The Psychometric Properties of the Norwegian version of Mullen Scales of Early Learning (MSEL) - Martinussen, Monica; Siqveland, Torill (PsykTestBarn, 2013)
Description: The Mullen Scales of Early Learning (MSEL) is a test designed to measure cognitive and motor abilities in children aged 0-68 months, and was first published in the USA in 1995 (Mullen, 1995). The test may be purchased from the test publisher Pearson. There is no test manual in Norwegian. The test includes five scales assessing the child’s gross motor skills, visual reception, fine motor skills, expressive language, and receptive language. In addition, a total score is calculated (The Early Learning Composite Score). Test administration takes between 30 and 60 minutes, depending on the child’s age. Psychologists or persons with equivalent certifications, who have received test administration training, are qualified to administer and use the test. Literature search: A systematic literature search of Norwegian and Scandinavian studies on the MSEL yielded 10 articles. However, none reported psychometric results for the test. Psychometrics: Two studies reported mean scores based on small clinical samples for the test, but no psychometric results were reported. Conclusion: Psychometric properties of the test based on Norwegian or Scandinavian samples have not been documented.